Accelerated aging of 28 Gb s−1 850 nm vertical-cavity surface-emitting laser with multiple thick oxide apertures. (19th February 2015) - Kropp, J R; Steinle, G; Schäfer, G; Shchukin, V A; Ledentsov, N N; Turkiewicz, J P; Zoldak, M
Abstract: 850 nm vertical-cavity surface-emitting lasers with multiple thick oxide apertures suitable for temperature-insensitive error free transmission at 28 Gb s −1 are subjected to accelerated aging at high current densities and chip temperatures. The devices withstand a 20% power change test at a high current density ( ) at an ambient temperature of for 2500 h. At 90– at this current density no degradation was observed up to 5000 h. We performed the studies at further elevated current densities and temperatures and define the acceleration factor as . The extrapolated lifetime for 20% power drop is estimated as 20 thousand years at 300 K at current density of which is sufficient for 28 Gb s −1 error-free temperature-insensitive data transmission.